Development aid and access to water and sanitation in Sub-Saharan Africa - Salami, A.; Stampini, M.; Kamara, A.; Sullivan, C.; Namara, Regassa E. (African Development Bank, 2011)
Providing safe drinking water and basic sanitation to citizens is one of the major challenges facing the African Governments. The issues of access to safe drinking water and improved sanitation is well articulated and prioritized in the various national, continental, and international policy documents, strategy papers, declarations, and conventions. And yet it is not clear if the provision of sustainable access to safe drinking water and basic sanitation has been given the requisite financial and other support by the SSA policy makers and donors. The principal objective of this paper is to compare countries' performance in the water and sanitation sector and analyze how effectively they used the development aid received for the Water and Sanitation sector (WSS). Much has been written on Development Aid Effectiveness, but the focus of attention has often been on how the donors operate, and how the recipients use the money. In this context, the paper utilised an innovative standardized measurement framework known as-the Watsan Index of Development Effectiveness (WIDE) - which compares drivers of progress with results achieved, and ranks African countries by the level of outcome obtained per unit of available input. In particular, how effectively they used the development aid received for the water and sanitation sector. The WIDE is made up of two composite information layers, the Resources (input drivers such as aid received, GDP, water resources, and governance level), and the Progress Outcomes (access to water, access to sanitation, and progress in the two). We also performed econometric analyses to explore the linkages between interventions designed to promote development, and the outcomes from that development process, in the water and sanitation sector. These analyses were further validated by presentation of the WSS sector situation of four case study countries namely, Kenya, Madagascar, Burkina Faso and Uganda.